Implementation Of Humanistic Learning In-State Elementary School Ii Bakalanpule - Kuswanto (INTERNATIONAL JOURNAL OF ECONOMICS, MANAGEMENT, BUSINESS, AND SOCIAL SCIENCE (IJEMBIS), 2022)
A humanistic approach to learning views students as whole individuals and has their uniqueness, potential, and intelligence. The humanistic approach seeks to humanize humans by developing students' potential and helping them achieve self-actualization through various models of humanist learning methods and strategies. This study aims to find out how the implementation of the humanistic approach in learning at the State Elementary School II Bakalanpule and what factors support and hinder the performance of the humanistic approach in learning at the State Elementary School II Bakalanpule. This study used qualitative research methods. Researchers obtained data from interviews, observations, and documentation. The data analysis technique used consisted of data reduction, data presentation, data analysis, and concluding. The method of checking the validity of the data uses triangulation in source, technical, and time triangulation. The study results indicate that the implementation of the humanistic approach in learning has been applied by the teachers of the State Elementary School II Bakalanpule through (a) education that is fun, free, does not restrain students, and emphasizes the activeness of students through several learning models. (b) supporting factors include complete facilities and a supportive school environment; students can be invited to work together in learning to create a humane learning atmosphere. (c) the inhibiting factor is the teacher's ability to operate IT